A long way to the electrode: how do Geobacter cells transport their electrons? - Bonanni, Pablo Sebastian (2012)
The mechanism of electron transport in Geobacter sulfurreducensbiofilms is a topic under intense study and debate. Although some proteins were found to be essential for current production, the specific role that each one plays in electron transport to the electrode remains to be elucidated and a consensus on the mechanism of electron transport has not been reached. In the present paper, to understand the state of the art in the topic, electron transport from inside of the cell to the electrode in Geobacter sulfurreducens biofilms is analysed, reviewing genetic studies, biofilm conductivity assays and electrochemical and spectro- electrochemical experiments. Furthermore, crucial data still required to achieve a deeper understanding are highlighted.